Psychogeography: A novel way of uncovering aspects of the corporate environment - Wardale, D.; Lord, Linley (2017)
© 2017 Academic Conferences Limited. All Rights Reserved. Psychogeography refers to the loose interface between psychology and geography. Specifically it examines how we impact on the environment and the environment impacts on us. As a process it involves intimately observing the environment and seeing what may have been previously unobserved. Participants then construct meaning from these observations. This paper describes how we used a time-limited psychogeography as a research method to determine if examining the physical environment participants inhabited would potentially enable them to identify enablers and potential barriers to career success. The focus was on academic women’s careers at a large public university in Western Australia and the use of a psychogeographic method was part of a larger research project on career success. Much of the women’s career development literature focuses on ‘fixing the women’ and not the system. To that end we wanted to use a method, in addition to interview questions, to uncover aspects of the corporate environment that might impact on women’s decisions to progress their careers. We asked participants to dérive, stroll or wander in pairs or threes within their university campus with a view to them to them observing any ‘career enablers and barriers at work’. Participants found the psychogeography exercise a novel approach to discovering and rediscovering their work environment. The findings revealed visible aspects of the work environment that had not previously been overt. These included participants’ appreciation of students having fun and a carnival atmosphere within the campus yet a simultaneous concern at the lack of quiet spaces to support scholarship and research; a disparity of investment in infrastructure improvements across various schools and faculties, which led to discussions of how disparately workload was managed by different managers; staff being segregated from students and other staff with security doors meaning for some that they spent a lot of their time escorting students, visitors and other staff to and from their offices; the number of steps at the university and the impact this would have on some people with a disability. One pleasing outcome of the psychogeography exercise was the level of energy and collegiality it generated. The exercise was conducted at an early stage in an eight-month career development program and its use heightened participant’s awareness of aspects of their work environment’s impact on career success that may have otherwise remained uncovered. Our view is that psychogeography is a valuable method to employ. It helped uncover aspects of university culture and enculturation to which many research participants had been previously oblivious.